Delivery of energy sustainability: Applications of the "STAR" protocol to the Sustainable Development Goal 7 index and its interaction analysis. (20th February 2023) - Zhao, Dandan; Cai, Jialiang; Shen, Lei; Elshkaki, Ayman; Liu, Junguo; Varis, Olli
Abstract: The establishment of Sustainable Development Goal (SDG) 7 within 17 SDGs of the United Nations' 2030 Agenda operationalizes the discussion of how to tackle energy challenges for the delivery of energy sustainability. Few studies have yet produced composite indices to capture the multi-dimensional nature of energy development as well as a general and operational framework for the evaluation of countries' overall performance on achieving SDG 7 remains absent. This hinders the quantitative assessment of interactions between SDGs at the specific target level. To address this gap, a composite SDG 7 index (SDG7I ) was developed with the applications of the "STAR" (Straightforwardness, Transparency, Availability, and Readiness) protocol in pursuance of universal energy sustainability. Further, the correlation structure between SDG 7 for energy and SDG 6 for water was performed. The assessment showed that a majority of countries around the world are on course to achieve universal energy services, but the implementation pace of service coverage in Sub-Saharan African countries needs to be substantially augmented. It was also found that the SDG7I score differed considerably between countries and territories, with 8.6% (20 out of 232) of the countries in the world belonging to high levels and 34.1% (79 out of 232) located in medium-high levels. 86% (67 out of 78) of the total interactions had interrelationships statistically, and the synergies largely outweighed the trade-offs relations, which accounted for 70% (54 out of 78) of the total globally. These experiments evinced that the "STAR" protocol has the great applicability to facilitating the evaluation of synergies and trade-offs between SDGs and their targets grounded in specific context with differential circumstances across the 2030 Agenda. The protocol also allows identifying the policy sensitivity of the SDG indicators and fosters multi-level governance and collaboration to leverage synergies and resolve trade-offs. Highlights: A composite SDG 7 index following the "STAR" protocol was developed. The SDG 7 index scores differed considerably between countries, in which 8.6% at high implementation level. 86% of total interactions between SDG 7 and SDG 6 had interrelationships statistically. The "STAR" protocol has the great applicability to facilitate the evaluation of synergies and trade-offs between SDGs.